2017
DOI: 10.1103/physrevb.95.054112
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic calculations of dislocation core energy in aluminium

Abstract: A robust molecular dynamics simulation method for calculating dislocation core energies has been developed. This method has unique advantages: it does not require artificial boundary conditions, is applicable for mixed dislocations, and can yield converged results regardless of the atomistic system size. Utilizing a high-fidelity bond order potential, we have applied this method in aluminium to calculate the dislocation core energy as a function of the angle β between the dislocation line and Burgers vector. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…Here, we illustrate this by calculating core energies of edge type of misfit dislocation in zinc-blende CdS [20] using the literature interatomic potential [21]. We also calculated dislocation energies for aluminium using exactly the same geometry as shown in Figure 1(a), and the same results were obtained [22].…”
Section: Dislocation Energymentioning
confidence: 88%
“…Here, we illustrate this by calculating core energies of edge type of misfit dislocation in zinc-blende CdS [20] using the literature interatomic potential [21]. We also calculated dislocation energies for aluminium using exactly the same geometry as shown in Figure 1(a), and the same results were obtained [22].…”
Section: Dislocation Energymentioning
confidence: 88%
“…Accordingly, the values of the core energy we find, although within the same order of magnitude as those commonly reported (see Refs. [77,78]), will nonetheless be different. For instance, we find that for fcc Al, over a few unit cells the V core converges to a value of about V core Al = −1.34 eV/Å.…”
Section: Energetic Considerationsmentioning
confidence: 98%
“…(32) is notionally analogous to the classical definition of the core energy (see Refs. [27,44,77]). The line energy of a dislocation is divided into two superposed terms: an elastic term associated with the Volterra dislocation's energy and a core energy term that accounts for the differences between the total and elastic terms.…”
Section: Energetic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered two types of vacancies, a collocated (covacancy) and a separated Schottky Li-F pair vacancy, as well as a a/2 110 edge dislocation dipole. The energies are determined with long time (32 ns) averages at low temperature (≈1K) based on the work of Zhou et al 46 which showed that this approach leads to estimates that are superior to energy minimization techniques.…”
Section: A Defect Energiesmentioning
confidence: 99%